Contemporary Management of B2B Applications with the Use of Web Applications - Zbigniew PIOTROWSKI; Mateusz MIKULSKI (Communications of International Proceedings, 2021)
This paper describes a sample solution for managing B2B applications using web application technology. When creating applications and systems, it turns out that it is necessary to create an administrative panel that allows you to manage specific human and system resources. The paper answers the question why it is worth using web applications in the form of management panels and provides an example of a dedicated solution using the React-Admin library.
Keywords: Management; administrator panel. web application; human resources; React-Admin.